Genome-wide identification, evolution and function analysis of UGTs superfamily in cotton - Sun, Liangqing; Zhao, Lanjie; Huang, Hui; Zhang, Yuexin; Wang, Junjuan; Lu, Xuke; Wang, Shuai; Wang, Delong; Chen, Xiugui; Chen, Chao; Guo, Lixue; Xu, Nan; et al. (Frontiers in Molecular Biosciences, 2022)
Glycosyltransferases mainly catalyse the glycosylation reaction in living organisms and widely exists in plants. UGTs have been identified from G. raimondii, G. arboreum and G. hirsutum. However, Genome-wide systematic analysis of UGTs superfamily have not been studied in G. barbadense. 752 UGTs were identified from 4 cotton species and grouped into 18 clades, of which R was newly discovered clades. Most UGTs were clustered at both ends of the chromosome and showed a heterogeneous distribution. UGT proteins were widely distributed in cells, with the highest distribution in chloroplasts. UGTs of the same clade shared similar intron/exon structural features. During evolution, the gene family has undergone strong selection for purification. UGTs were significantly enriched in "transcriptional activity (GO:0016758)" and "metabolic processes (GO:0008152)". Genes from the same clade differed in function under various abiotic stresses. The analysis of cis-acting element and qRT–PCR indicated that GHUGTs play important roles in plant growth, development and abiotic stress. We further found that GHUGT74-2 plays an important role under submergence. The study broadens the understanding of UGTs in terms of gene characteristics, evolutionary processes, and gene function in cotton and provides a new way to systematically and globally understand the structure–function relationship of multigene families in the evolutionary process.